1998
DOI: 10.1007/bf02303778
|View full text |Cite
|
Sign up to set email alerts
|

Detection of eIF4E gene amplification in breast cancer by competitive PCR

Abstract: Overexpression of eIF4E was associated with eIF4E gene amplification in breast cancer specimens. No overexpression or gene amplification was detected in benign breast tissues. eIF4E gene amplification may be one mechanism for eIF4E oncoprotein overexpression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 14 publications
2
42
0
Order By: Relevance
“…The role of initiation factors in the progression to a malignant phenotype is reported in many cancers, including, breast, head and neck, liver, prostate, bladder, gastric, colon, ovarian, glioma, lymphoma, non-small cell lung carcinoma, cervical, small intestine, and melanoma (20,(23)(24)(25). This has highlighted eIFs, notably eIF4E, as indicative of poor prognosis.…”
Section: Discussionmentioning
confidence: 97%
“…The role of initiation factors in the progression to a malignant phenotype is reported in many cancers, including, breast, head and neck, liver, prostate, bladder, gastric, colon, ovarian, glioma, lymphoma, non-small cell lung carcinoma, cervical, small intestine, and melanoma (20,(23)(24)(25). This has highlighted eIFs, notably eIF4E, as indicative of poor prognosis.…”
Section: Discussionmentioning
confidence: 97%
“…24,25 Inhibition of COX-2 by MEK inhibitors is unlikely to explain the cytostatic effects of the MEK inhibitors, however, because other investigators have shown that COX-2 inhibitors are cytotoxic to NSCLC cells, with and without chemotherapy. 26,27 In contrast to PD98059, nonspecific effects of DNMs toward inhibition of other targets have not been described. Future studies will determine if DNMs and small molecule MEK inhibitors have differential effects on inhibition of COX-1, COX-2, or aryl hydrocarbon receptors, and whether this contributes to the different cellular responses of NSCLC cells to inhibition of the MEK/ERK pathway by MEK inhibitors or DNMs.…”
Section: Discussionmentioning
confidence: 99%
“…A, activity that can overcome the cellular barrier of apoptosis resulting from MYC-induced oncogenic stress (12,13). eIF4E gene amplification has been reported in human breast cancer and in head and neck cancer specimens compared with noncancerous control samples (14,15).…”
Section: Eif4e In Cancer Initiation and Progressionmentioning
confidence: 99%